A Spelling Lesson Plan Model to Indonesian Young Learners Using Peer-Tutoring Approach - Saraswati Diana; Engliana Seok; Leni Tiwiyanti (Universitas Nasional, 2021)
The article is conceptualized a lesson plan for teaching English spelling to young learners at primary school. The underlying strategy is pairing student and another peer student instead of teacher-student. Previous and present studies have shown that teaching spelling to learners can enhance other language skills, to name a few, i.e., reading and listening. Thus far, little to be found a practical lesson plan provided in the Indonesian context. Having this article is hoped to be a trigger for a new idea to consider student-student activity into the material design and its methods of teaching in the EFL context. The plan will be particularly helpful for the educators who seek perspectives in teaching and researching spelling to young learners.